Antidepressant Use in Depressed Women During Pregnancy and the Risk of Preterm Birth: A Systematic Review and Meta-Analysis of 23 Cohort Studies - Chang, Qing; Ma, Xiao-Yu; Xu, Xin-Rui; Su, Han; Wu, Qi-Jun; Zhao, Yu-Hong (Frontiers in Pharmacology, 2020)
Objective: The associations between maternal use of antidepressant during pregnancy and preterm birth (PTB) has been the subject of much discussion and controversy. The aim of the present study was to systematically review the association between antidepressant use during pregnancy and the risk of PTB, especially in depressed women. Methods: A computerized search was conducted in PubMed, PsycINFO, and Embase before June 30, 2019, supplemented with a manual search of the reference lists, to identify original research regarding PTB rates in women taking antidepressants during pregnancy. A random-effects model was used to calculate the summarized relative risks (RRs) and 95% confidence intercals (CIs). The potential for publication bias was examined through Begg’ s and Egger’ s tests. Results: A total of 2279 articles were reviewed, 23 of which were selected. The risk of PTB was increased in women with depression [1.58 (1.23−2.04)] and in the general pregnant female population [1.35 (1.11−1.63)] who used antidepressants during pregnancy. Similar results were observed in depressed women treated with Selective Serotonin Reuptake Inhibitors (SSRIs) during pregnancy [1.46 (1.32−1.61)]. There was no significantly increased risk of PTB observed with SSRI use in the general pregnant female population [1.25 (1.00−1.57)], and the heterogeneity of these studies was high. Conclusions: The results of this meta-analysis indicate maternal antidepressant use is associated with a significantly increased risk of PTB in infants. Health care providers and pregnant women must weigh the risk-benefit potential of these drugs when making decisions about whether to treat with antidepressant during pregnancy.